Remote ECG Monitoring by ECG247 Smart Heart Sensor - Jarle Jortveit; Rune Fensli (International Journal of Telemedicine and Applications)
Background. Heart rhythm disorders are common and may be associated with serious complications. The quality of the ECG signal is crucial to detect and classify arrhythmias. Most available devices for assessment arrhythmias do not allow for remote monitoring. The Norwegian ECG247 Smart Heart Sensor is a new remote patch monitor developed to simplify the assessment of arrhythmias. This study was aimed at evaluating the quality of the ECG signal from the ECG247 Smart Heart Sensor compared to standard 12-lead ECG. Methods. ECG recordings with ECG247 Smart Heart Sensor and a standard 12-lead ECG recorder were performed in 97 volunteers at Sorlandet Hospital, Arendal, Norway, in 2019. All ECGs were analysed by two independent cardiologists. Results. A total of 97 participants (53% men, age 48 (±14) years) were included in the study. The ability for both systems to use recorded ECG data for arrhythmia detection was good (100%). The quality of the P-wave (mean score 1.1 vs. 1.5) and the QRS complex (mean score 1.0 vs. 1.0) from the ECG247 Smart Heart Sensor and that from the 12-lead ECG were comparable (scale: 1: extremely good, 9: not accepted). Noise artefacts were a minor issue in all recordings. Conclusions. The ECG quality from the ECG247 Smart Heart Sensor was comparable to the ECG quality from the standard 12-lead ECG. The ECG247 Smart Heart Sensor may enable easy and remote diagnostics of heart rhythm disorders. This trial is registered with NCT04700865.